Clinical effectiveness and acceptability of structured group psychoeducation versus optimised unstructured peer support for patients with remitted bipolar disorder (PARADES): a pragmatic, multicentre, observer-blind, randomised controlled superiority trial. (November 2016) - Morriss, Richard; Lobban, Fiona; Riste, Lisa; Davies, Linda; Holland, Fiona; Long, Rita; Lykomitrou, Georgia; Peters, Sarah; Roberts, Christopher; Robinson, Heather; Jones, Steven; ,
Summary: Background: Group psychoeducation is a low-cost National Institute for Health and Care Excellence-recommended treatment for bipolar disorder. However, the clinical effectiveness and acceptability of this intervention are unclear compared with unstructured peer support matched for delivery and aim of treatment, and for previous bipolar history. We aimed to assess the clinical effectiveness and acceptability of structured group psychoeducation versus optimised unstructured peer support for patients with remitted bipolar disorder. Methods: We did this pragmatic, multicentre, parallel-group, observer-blind, randomised controlled superiority trial at eight community sites in two regions in England. Participants aged 18 years or older with bipolar disorder and no episode in the preceding 4 weeks were recruited via self-referral or secondary care referral. Participants were individually randomly assigned (1:1), via a computer-generated stochastic allocation sequence, to attend 21 2-h weekly sessions of either structured group psychoeducation or optimised unstructured peer support. Randomisation was minimised by number of previous episodes (one to seven, eight to 19, or ≥20) and stratified by clinical site. Outcome assessors were masked to group allocation. The primary outcome was time from randomisation to next bipolar episode, with planned moderator analysis of number of previous bipolar episodes and qualitative interview of participant experience. We did analysis by intention to treat. This trial is registered with the International Standard Randomised Controlled Trial registry, number ISRCTN62761948. Findings: Between Sept 28, 2009, and Jan 9, 2012, we randomly assigned 304 participants to receive psychoeducation (n=153) or peer support (n=151); all (100%) participants had complete primary outcome data. Attendance at psychoeducation groups was higher than at peer-support groups (median 14 sessions [IQR three to 18] vs nine sessions [two to 17]; p=0·026). At 96 weeks, 89 (58%) participants in the psychoeducation group had experienced a next bipolar episode compared with 98 (65%) participants in the peer-support group; time to next bipolar episode did not differ between groups (hazard ratio [HR] 0·83, 95% CI 0·62–1·11; p=0·217). Planned moderator analysis showed that psychoeducation was most beneficial in participants with few (one to seven) previous bipolar episodes (χ 2 ; HR 0·28, 95% CI 0·12–0·68; p=0·034). Four (1%) participants (one in the psychoeducation group and three in the peer-support group) died during follow-up; these deaths were deemed unrelated to the study interventions or procedures. Interpretation: Structured group psychoeducation was no more clinically effective than similarly intensive unstructured peer support, but was more acceptable and improved outcome in participants with fewer previous bipolar episodes. Optimum provision of structured psychological interventions, such as group psychoeducation, early in the course of bipolar disorder might have important benefits on the course of illness, and merits further research. Funding: National Institute for Health Research.